Pembuatan Media Pembelajaran Virtual Berbasis Construct 2 - Mashur, Mohan Taufiq; Jaelani, Jaelani; Akbar, M. Zulfani (Carmin: Journal of Community Service, 2024)
The community service activity "Creating Construct 2-Based Virtual Learning Media" was carried out on Saturday, October 8, 2021. This service activity was attended by 203 participants consisting of 26 people (12.8%) lecturers, 25 people (12, 3%) teachers, 149 (73.4%) students, and 3 (1.5%) alumni. Activities are carried out online and offline. Online using Zoom, while offline it was held on the 3rd floor of building A, Faculty of Tarbiyah and Teacher Training, Mataram State Islamic University. Activities are carried out through several stages, namely; opening, the core activity is the provision of materials or presentations on making virtual learning media using the construct 2 application, question and answer with all participants both offline and online, and ends with prayer and closing. This service activity succeeded in providing understanding to all participants, 187 (92.1%) of whom had never used the Construct 2 application or program in making virtual-based learning media, especially using the Construct 2 application.